Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12272-011-0913-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cannabidiolic acid and cannabidiol on contractility of the gastrointestinal tract of Suncus murinus

Abstract: Cannabidiol (CBD) has been shown to inhibit gastrointestinal (GI) transit in pathophysiologic in vivo models, while having no effect in physiologic controls. The actions of the precursor of CBD, cannabidiolic acid (CBDA), have not been investigated in the GI tract. The actions of these phytocannabinoids on the contractility of the GI tract of Suncus murinus were investigated in the current study. The effects of CBDA and CBD in resting state and pre-contracted isolated intestinal segments, and on the contractil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…There is also in vitro evidence that CBDA activates the transient receptor potential (TRP) cation channels, TRPV1 (EC 50 = 19.7 ± 3.9 μM) and TRPA1 (EC 50 = 12.0 ± 8.8 μM), and antagonizes TRPM8 (IC 50 = 1.6 ± 0.4 μM) (De Petrocellis et al ., ; De Petrocellis et al ., ). Furthermore, CBDA has been found to affect the contractility of gastrointestinal tissue of S. murinus in vitro , as indicated by its ability, at 10 μM, to reduce both the magnitude of contractions induced by carbachol or by electrical field stimulation and the tension of intestinal segments that had been pre‐contracted with potassium chloride (Cluny et al ., ). In addition, Takeda et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is also in vitro evidence that CBDA activates the transient receptor potential (TRP) cation channels, TRPV1 (EC 50 = 19.7 ± 3.9 μM) and TRPA1 (EC 50 = 12.0 ± 8.8 μM), and antagonizes TRPM8 (IC 50 = 1.6 ± 0.4 μM) (De Petrocellis et al ., ; De Petrocellis et al ., ). Furthermore, CBDA has been found to affect the contractility of gastrointestinal tissue of S. murinus in vitro , as indicated by its ability, at 10 μM, to reduce both the magnitude of contractions induced by carbachol or by electrical field stimulation and the tension of intestinal segments that had been pre‐contracted with potassium chloride (Cluny et al ., ). In addition, Takeda et al .…”
Section: Discussionmentioning
confidence: 97%
“…There is also in vitro evidence that CBDA activates the transient receptor potential (TRP) cation channels, TRPV1 (EC50 = 19.7 Ϯ 3.9 mM) and TRPA1 (EC50 = 12.0 Ϯ 8.8 mM), and antagonizes TRPM8 (IC50 = 1.6 Ϯ 0.4 mM) (De Petrocellis et al, 2008;De Petrocellis et al, 2011). Furthermore, CBDA has been found to affect the contractility of gastrointestinal tissue of S. murinus in vitro, as indicated by its ability, at 10 mM, to reduce both the magnitude of contractions induced by carbachol or by electrical field stimulation and the tension of intestinal segments that had been pre-contracted with potassium chloride (Cluny et al, 2011). In addition, Takeda et al (2008) have reported that CBDA (IC50 = 2 mM) is a selective inhibitor of COX-2, an enzyme expressed by cells undergoing inflammation; however, Ruhaak et al (2011) found more recently that CBDA did not inhibit this enzyme, but rather COX-1 (IC50 = 4.7 ¥ 10 -4 M), prompting a need for further research.…”
Section: Figurementioning
confidence: 98%
“…However, the lack of locomotor activity modulation in this test (as measured by line crosses) suggests this observation may still be indicative of an anxiolytic-like effect. Cannabidiol (CBD), produced by spontaneous decarboxylation of CBDA (Cluny et al 2011), has well-documented anxiolytic-like effects in both animals and humans (reviewed by de Schier et al 2012) which appears to be primarily facilitated by 5-HT 1A R-mediated neurotransmission (Campos et al 2012). However, to the best of our knowledge, only a single study of the anxiolytic-like effects of CBDA has been published to date.…”
Section: Discussionmentioning
confidence: 99%
“…At 1 μM, both CBD and CBDA have also been shown to produce a significant downward shift in log concentration–response curve of the GPR55 agonist, L‐α‐lysophosphatidylinositol, for its stimulation of ERK1/2 phosphorylation in human GPR55‐transfected HEK293 cells (Anavi‐Goffer et al ., ). Furthermore, CBDA has been found to affect the contractility of gastrointestinal tissue of house musk shrews in vitro , as indicated by its ability, at 10 μM, to reduce both the magnitude of contractions induced by carbachol or by electrical field stimulation and the tension of intestinal segments that had been pre‐contracted with potassium chloride (Cluny et al ., ). In addition, Takeda et al .…”
Section: Introductionmentioning
confidence: 97%